Conductance, Laplacian and Mixing Rate in Discrete Dynamical Systems - Fernandes, Sara (2012)
We introduce the notion of conductance in discrete dynamical systems defined by iterated maps of the interval. Our starting point is the notion of conductance in the graph theory. We pretend to apply the known results in this new context.